Russianisms in Costa Rican Online Newspapers - Sánchez Murillo, Julio (2023)
The presence of Russianisms is examined in ten Costa Rican online newspapers in the period 2015-2020. An inventory of Russian words is established and the areas of influence of this language are defined. In addition, the graphic, grammatical and orthotypographical procedures for integrating these terms and their condition as lexical loanwords are analyzed.